PENERAPAN MODEL PEMBELAJARAN TEAMS GAMES TOURNAMENTS (TGT) UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK MATA PELAJARAN PENDIDIKAN PANCASILA MATERI MENGHARGAI IDENTITAS MASYARAKAT KELAS IV B DI SD NEGERI 47 PALEMBANG - Nurzanah, Maya Sinta; Hudaidah, Hudaidah; Saputri, Helen (JURNAL PENDIDIKAN DASAR PERKHASA: Jurnal Penelitian Pendidikan Dasar, 2025)
This study aims to determine whether the Teams Games Tournaments (TGT) learning model can improve the learning outcomes of Grade IV B students in the subject of Pancasila Education at SD Negeri 47 Palembang, particularly in the topic of national identity. This research employed a Classroom Action Research (CAR) approach based on Kurt Lewin’s paradigm. A total of 33 students from class IV B participated in the study. Data were collected through interviews, observation sheets, and written tests. Pre-cycle learning outcome data showed that thirteen students (39.4%) did not meet the minimum learning mastery criteria, while twenty students (60.6%) did. In Cycle I, sixteen students (48.5%) achieved mastery, with an average score of 75.75. In Cycle II, thirty students (90.9%) achieved mastery, an increase of 42.4%, with an average score of 84.54. Furthermore, students’ learning activity in Cycle II averaged 7.93 (Active), an increase of 1.03 from Cycle I, which averaged 6.90 (Less Active). Based on the findings, the TGT learning model has been shown to improve the learning outcomes of Grade IV B students at SD Negeri 47 Palembang.